PET wig raw yarn with excellent mechanical property and antistatic property and manufacturing method thereof
Patent Information
- Application Number
- KR1020250199287
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2045-12-15
Smart Images

Figure 112025141600126-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a PET wig yarn with excellent mechanical properties and antistatic properties and a method for manufacturing the same. More specifically, the invention relates to a PET wig yarn with excellent mechanical properties and antistatic properties and a method for manufacturing the same, wherein the yarn is manufactured into a filament using a master chip containing PET resin as a main component to possess excellent mechanical properties and curling properties, while also forming an antistatic coating layer covering the surface of the PET resin to improve antistatic properties and durability. Background Technology
[0002] Generally, wig fibers are manufactured using synthetic fiber materials such as PVC (polyvinyl chloride), modacrylate, PET (polyethyleneterephthalate), and PP (polypropylene). These synthetic fiber materials are continuously being developed to satisfy functional and aesthetic elements, such as flame retardancy, heat resistance, curl formation, gloss, and tactile properties.
[0003] Among these, PVC is a widely used wig fiber developed by melt spinning, offering good shape stability and a pleasant feel, but it has the disadvantage of being heavy and lacking volume. Additionally, modacrylic takes advantage of its flame retardancy to form curls well and provide volume, but it wrinkles easily and is lightweight, while acrylic fibers have a low glass transition temperature, which leads to reduced thermal stability.
[0004] In contrast, fibers primarily composed of polyester, represented by polyethylene terephthalate with excellent heat resistance, are evaluated as superior materials compared to other fibers used for wigs due to their advantages, such as excellent curling ability and style stability resulting from a high glass transition temperature, good elasticity, color and gloss, and ease of setting after heat fixation.
[0005] However, polyester resins have disadvantages such as poor texture due to high elasticity, difficulty in dyeing, entanglement due to static electricity, and rapid combustion after ignition, so improvements such as imparting flame retardancy are necessary to ensure a wide range of applications.
[0006] Methods to improve the flame retardancy of such polyester fibers include adding reactive flame retardants along with the raw materials during polyester polymerization to impart flame retardancy, or mixing flame retardant additives with the polyester resin during molding. In this case, flame retardant additives include halogen-containing compounds, mixtures of metal oxides, nitrogen-containing compounds, and phosphorus-containing compounds. Among these, halogen-based flame retardants facilitate the development of flame retardancy relatively easily but cause issues such as toxicity and discoloration, while phosphorus-based flame retardants have problems such as low inherent thermal stability and poor processability due to the difficulty in increasing the degree of polymerization.
[0007] Therefore, due to the high heat resistance required for artificial hair, there are problems such as increased costs, reduced productivity, or deterioration of physical properties resulting from processing at high temperatures, increasing the flame retardant content, or extending the flame retardant treatment time.
[0008] Recently, active research is being conducted to manufacture various wig fibers that are harmless to the human body while improving workability, processability, heat resistance, flame retardancy, and other physical properties to expand their range of applications. However, wig fibers made of PET resin-based polyester resins present a problem where mechanical properties and curling performance deteriorate when adequate flame retardancy is achieved. Additionally, while polypropylene-based wig fibers offer excellent curling performance, they suffer from poor durability due to inferior mechanical properties. Prior art literature
[0009] Republic of Korea Published Patent Application No. 10-2011-0108974 (Published Oct. 06, 2011) The problem to be solved
[0010] The objective of the present invention is to provide a PET wig yarn with excellent mechanical properties and antistatic properties, and a method for manufacturing the same, which is manufactured into a filament using a master chip containing PET resin as the main component, and which has excellent mechanical properties and curling properties, while also having an antistatic coating layer covering the surface of the PET resin to improve antistatic properties and durability. means of solving the problem
[0011] A method for manufacturing a PET wig yarn having excellent mechanical properties and antistatic properties according to an embodiment of the present invention is characterized by comprising: a wig yarn body comprising 20 to 40 wt% of a flame retardant, 0.1 to 5.0 wt% of a heat stabilizer, 0.1 to 3.0 wt% of a process stabilizer, 5 to 15 wt% of a strength reinforcing agent, and the remainder being PET resin; and an antistatic coating layer formed to cover the surface of the wig yarn body, comprising 10 to 30 wt% of a reactive monomer, 1 to 10 wt% of a photoinitiator, 5 to 25 wt% of an antistatic agent, 0.1 to 3 wt% of a leveling agent, 10 to 40 wt% of a photopolymerizable urethane acrylate oligomer, and the remainder being a conductive polymer.
[0012] The strength reinforcing agent comprises one or more selected from talc, alumina, calcium carbonate, magnesium carbonate, magnesia, calcium silicate, glass fiber, titanium oxide, and antimony oxide, and the strength reinforcing agent comprises a first strength reinforcing agent having an average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm, wherein the first strength reinforcing agent is added in an amount of 60 to 80 weight% and the second strength reinforcing agent is added in an amount of 20 to 40 weight%.
[0013] The above PET resin comprises a high-viscosity PET (polyethylene terephthalate) resin with an intrinsic viscosity of 0.75 to 0.90 and a low-viscosity PET resin with an intrinsic viscosity of 0.50 to 0.60, wherein the high-viscosity PET resin comprises 80 to 95 weight% and the low-viscosity PET resin comprises 5 to 20 weight%.
[0014] The above antistatic coating layer has a thickness of 10 to 500 nm.
[0015] The above conductive polymer includes one or more selected from polyaniline, polypyrrole, polythiophene, poly(3,4-ethylenethiophene), derivatives thereof, and copolymers thereof.
[0016] A PET wig yarn having excellent mechanical properties and antistatic properties according to an embodiment of the present invention comprises: (a) a step of preparing a master chip comprising 20 to 40 wt% of a flame retardant, 0.1 to 5.0 wt% of a heat stabilizer, 0.1 to 3.0 wt% of a process stabilizer, 5 to 15 wt% of a strength reinforcing agent, and the remainder being PET resin; (b) a step of supplying the master chip to a spinneret in a state of melting and kneading, and then compressing and spinning to form a filament; (c) a step of drafting the filament at a draft ratio of 10 to 50 times; and (d) a step of forming an antistatic coating layer by coating an antistatic coating composition on the surface of the drafted filament and then drying it; wherein, in step (d), the antistatic coating layer comprises 10 to 30 wt% of a reactive monomer, 1 to 10 wt% of a photoinitiator, 5 to 25 wt% of an antistatic agent, 0.1 to 3 wt% of a leveling agent, 10 to 40 wt% of a photopolymerizable urethane acrylate oligomer, and the remainder being a conductive polymer.
[0017] In step (a) above, the PET resin comprises a high-viscosity PET (polyethylene terephthalate) resin having an intrinsic viscosity of 0.75 to 0.90 and a low-viscosity PET resin having an intrinsic viscosity of 0.50 to 0.60, wherein the high-viscosity PET resin comprises 80 to 95 weight% and the low-viscosity PET resin comprises 5 to 20 weight%.
[0018] In step (d) above, the antistatic coating layer has a thickness of 10 to 500 nm.
[0019] In step (d) above, the conductive polymer comprises one or more selected from polyaniline, polypyrrole, polythiophene, poly(3,4-ethylenethiophene), derivatives thereof and copolymers thereof. Effects of the invention
[0020] The PET wig yarn with excellent mechanical properties and antistatic properties according to the present invention and the method for manufacturing the same are manufactured into filaments using a master chip containing PET resin as a main component, thereby having excellent mechanical properties and curling properties, while also forming an antistatic coating layer covering the surface of the PET resin to improve antistatic properties and durability.
[0021] In addition, the PET wig yarn with excellent mechanical properties and antistatic properties according to the present invention and the method for manufacturing the same provide an excellent antistatic effect through an antistatic coating layer covering the surface of the wig yarn body. This not only prevents the problem of wig hair lifting due to static electricity but also enables improved curl retention and curl elasticity by ensuring excellent mechanical properties and curling ability through superior strength and durability.
[0022] As a result, the PET wig yarn with excellent mechanical properties and antistatic properties according to the present invention and the method for manufacturing the same exhibit a strength of 3.5 to 4.0 g / de and an elongation of 70 to 75% when the fineness is 50 denier (de), thereby exhibiting excellent curl formation properties as well as excellent curl retention properties. Brief explanation of the drawing
[0023] FIG. 1 is a schematic diagram showing a PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention. FIG. 2 is a process flowchart showing a method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention. Specific details for implementing the invention
[0024] Preferred embodiments of the present invention are described in detail below. This description is intended to enable a person skilled in the art to easily practice the invention, and does not imply that the technical scope and concept of the present invention are limited thereby.
[0025] FIG. 1 is a schematic diagram showing a PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention.
[0026] As shown in FIG. 1, a PET wig yarn (100) with excellent mechanical properties and antistatic properties according to an embodiment of the present invention includes a wig yarn body (120) and an antistatic layer (140).
[0027] The wig yarn body (120) comprises 20 to 40 weight% flame retardant, 0.1 to 5.0 weight% heat stabilizer, 0.1 to 3.0 weight% process stabilizer, 5 to 15 weight% strength reinforcing agent, and the remainder being PET resin.
[0028] Flame retardants can be used by mixing one or two types selected from phosphorus-based flame retardants and polymeric bromine-based flame retardants, and more preferably, polymeric bromine-based flame retardants are used.
[0029] In the present invention, it is preferable that the flame retardant be added in a content ratio of 20 to 40 weight percent of the total weight of the wig yarn body (120), and more preferable that it be added in a content ratio of 25 to 35 weight percent. If the amount of such flame retardant added is less than 20 weight percent of the total weight of the wig yarn body (120), sufficient flame retardancy may not be secured, and if it is added in excess of 40 weight percent, there is a problem of reduced mechanical properties.
[0030] A polymeric bromine-based flame retardant may be used having a bromine content of 40 to 80 weight%, preferably 55 to 75 weight%, and more preferably 58 to 70 weight%. In this case, the polymeric bromine-based flame retardant has a weight-average molecular weight (Mw) of 10,000 to 120,000, preferably 30,000 to 95,000, and more preferably 55,000 to 95,000, which is advantageous in terms of the self-extinguishing properties, melt-dripping inhibition properties, fiber formation properties, and good heat deformation temperature resistance of the wig yarn. If the Mw of the polymeric bromine-based flame retardant is less than 10,000, self-extinguishing properties may be obtained, but the anti-dripping function may not be able to be exerted upon ignition.
[0031] Specifically, one or more selected from polystyrene bromo flame retardants, polybromoepoxy flame retardants, polybromophenoxy flame retardants, polybromocarbonate flame retardants, and polybromoacrylate flame retardants may be used, and preferably, a polybromoepoxy or polybromophenoxy flame retardant composed of a polymer of brominated bisphenol A diglycidyl ether and brominated bisphenol A is used.
[0032] Polymeric bromine-based flame retardants have a melting temperature of 200 to 230°C, and the melt spinning temperature of PET resin is in the range of approximately 270 to 330°C. Since the melting temperature of PET resin is about 70 to 100°C higher than that of the flame retardant, thermal decomposition is likely to occur as the materials are mixed under high shear force inside the cylinder of the extruder. When thermal decomposition occurs, three-dimensional crosslinking materials are formed, causing gelation. If the product is operated for a long time, these materials clog the fine nozzle holes, making spinning impossible. Fine materials that pass through the nozzle holes accumulate around them, eventually acting as an obstacle to polymer flow, causing fine or curved yarns and leading to yarn breakage. Consequently, this results in reduced productivity and uneven fineness of the produced synthetic yarn.
[0033] Heat stabilizers and process stabilizers are added to minimize the generation of radicals, which are resin pyrolysis products of the wig yarn body (120), to improve compatibility between the PET resin and the flame retardant, and to prevent the flame retardant from adhering to metal surfaces such as cylinders, screws, and nozzles of the melt extruder. At this time, Irganox 1010 may be used as the heat stabilizer and Struktol TR 065 may be used as the process stabilizer, but are not limited thereto. Significant improvement effects can be obtained when using polybromoepoxy flame retardant or polybromophenoxy flame retardant as these heat stabilizers and process stabilizers.
[0034] It is preferable that the heat stabilizer be added in a content ratio of 0.1 to 5.0 weight% of the total weight of the wig yarn body (120), and it is preferable that the process stabilizer be added in a content ratio of 0.1 to 3.0 weight% of the total weight of the wig yarn body (120).
[0035] A strength reinforcing agent is added to reinforce the strength of the wig yarn body (120). This strength reinforcing agent includes one or more selected from talc, alumina, calcium carbonate, magnesium carbonate, magnesia, calcium silicate, glass fiber, titanium oxide, and antimony oxide.
[0036] It is preferable that the strength reinforcing agent be added in a content ratio of 5 to 15 weight percent of the total weight of the wig yarn body (120), and more preferable that it be added in a content ratio of 8 to 12 weight percent. If the amount of such strength reinforcing agent added is less than 5 weight percent of the total weight of the wig yarn body (120), the strength reinforcing effect cannot be properly exerted, and if it is added in excess of 15 weight percent, there is a high risk that physical properties such as heat resistance will be reduced.
[0037] Such strength reinforcing agents may include a first strength reinforcing agent having an average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm. In this case, it is preferable to add 60 to 80 weight% of the first strength reinforcing agent and 20 to 40 weight% of the second strength reinforcing agent. In this way, when a first strength reinforcing agent having a relatively small average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm, which is relatively larger than the first strength reinforcing agent, are mixed and added, the dispersibility of the relatively large second strength reinforcing agent and the relatively small first strength reinforcing agent is greatly improved, thereby improving strength uniformity.
[0038] The PET (polyethylene terephthalate) resin comprises a high-viscosity PET (polyethylene terephthalate) resin with an intrinsic viscosity of 0.75 to 0.90 and a low-viscosity PET resin with an intrinsic viscosity of 0.50 to 0.60, wherein it is preferable to comprise 80 to 95 weight% of the high-viscosity PET resin and 5 to 20 weight% of the low-viscosity PET resin.
[0039] It is more preferable to use a mixture of high-viscosity and low-viscosity PET (polyethylene terephthalate) resins, wherein the difference in intrinsic viscosity is 0.15 to 0.25, most preferably 0.17 to 0.22. At this time, if the difference in intrinsic viscosity is less than 0.15 or greater than 0.25, it may be difficult to manufacture a PET wig yarn (100) having the desired curling properties and mechanical properties.
[0040] An antistatic coating layer (140) is formed to cover the surface of the wig yarn body (120). This antistatic coating layer (140) may be formed to cover the entire surface of the wig yarn body (120) to seal the wig yarn body (120). Additionally, the antistatic coating layer (140) may be formed to locally cover a portion of the surface of the wig yarn body (120), so that a portion of the antistatic coating layer (140) is exposed to the outside.
[0041] This antistatic coating layer (140) is formed to cover the surface of the wig yarn body (120), thereby preventing static electricity from occurring and improving durability.
[0042] To this end, the antistatic coating layer (140) comprises 10 to 30 weight% of a reactive monomer, 1 to 10 weight% of a photoinitiator, 5 to 25 weight% of an antistatic agent, 0.1 to 3 weight% of a leveling agent, 10 to 40 weight% of a photopolymerizable urethane acrylate oligomer, and the remaining amount of a conductive polymer.
[0043] The reactive monomer may have one or more acrylate, methacrylate, or vinyl groups in its molecular structure and may be a monomer having 1 to 3 functional groups or more various functional groups, and the amount of 1 to 3 functional monomers, etc., may be adjusted considering the working viscosity, substrate adhesion, and scratch resistance of the resin composition. In addition, it is desirable for the reactive monomer to have high tensile strength and a low curing shrinkage rate.
[0044] These reactive monomers may include one or more selected from monofunctional monomers, such as 2-hydroxypropyl (meth)acrylate, 2-phenoxyethyl acrylate, ethylene oxide addition type phenoxyethyl acrylate, 2-(2-ethoxy)ethyl acrylate, nonylphenyl acrylate, epoxy monoacrylate, and oxyethylphenol acrylate.
[0045] It is preferable that the reactive monomer be included in an amount of 10 to 30 weight percent of the total weight of the antistatic coating layer. If the reactive monomer is less than 10 weight percent of the total weight of the antistatic coating layer (140), there is a problem with reduced curability, and if it exceeds 30 weight percent, the content of the conductive polymer is reduced relatively, and there is a concern that the antistatic effect may be reduced.
[0046] The photoinitiator may be a benzophenone-based compound such as 1-hydroxycyclohexylphenyl ketone. More specifically, the photoinitiator may be acetophenones, benzophenones, miclerbenzoylbenzoate, α-amyloxime esters, and thioxantones, but is not limited thereto.
[0047] It is preferable that the photoinitiator be added in a content ratio of 1 to 10 weight percent of the total weight of the antistatic coating layer. If the amount of photoinitiator added is less than 1 weight percent of the total weight of the antistatic coating layer (140), problems such as the curing reaction not occurring or a long reaction time being required, which makes it unsuitable for actual processes, and the disadvantage of not producing sufficient hardness may occur, and if it exceeds 10 weight percent, unreacted initiator may remain as an impurity and reduce durability.
[0048] Antistatic agents are added to prevent the generation of static electricity. Such antistatic agents may include one or more selected from non-ionic amine-based antistatic agents, polyhydric alcohol fatty acid ester antistatic agents, non-ionic amino-based antistatic agents, aliphatic amide-based antistatic agents, ionic-based antistatic agents, ionic polymer-based antistatic agents, quaternary ammonium-based antistatic agents, ionic complex-based antistatic agents, lithium amide-based antistatic agents, and photocurable antistatic agents.
[0049] It is preferable that the antistatic agent be added in a content ratio of 5 to 25 weight percent of the total weight of the antistatic coating layer (140), and more preferable that it be added in a content ratio of 10 to 15 weight percent. If the amount of antistatic agent added is less than 5 weight percent of the total weight of the antistatic coating layer (140), the effect of lowering surface resistance is negligible, and there is a concern that static electricity generation may not be suppressed. If it exceeds 25 weight percent, the viscosity is too low, and there is a problem of reduced adhesion and durability.
[0050] Leveling agents play a role in providing surface smoothness and surface slip functions, while simultaneously improving scratch resistance.
[0051] These leveling agents may include one or more selected from silicone acrylate-based leveling agents, non-silicon acrylate-based leveling agents, and acrylate polysiloxane-based leveling agents. It is preferable that the leveling agent be added in a content ratio of 0.1 to 3 weight percent of the total weight of the antistatic coating layer (140). If the amount of leveling agent added is less than 0.1 weight percent of the total weight of the antistatic coating layer (140), there is a high risk that the surface smoothness and surface slip function will not be properly exhibited, and if it exceeds 3 weight percent, it causes an increase in cost and a problem of excessively lowering the viscosity.
[0052] It is preferable to use a photopolymerizable urethane acrylate oligomer having 2 to 6 functional groups and a weight-average molecular weight (Mw) within 1,000 to 2,000. If the weight-average molecular weight (Mw) of the photopolymerizable urethane acrylate oligomer is less than 1,000, the antistatic coating layer is prone to cracking and has poor adhesion, and if the weight-average molecular weight (Mw) of the photopolymerizable urethane acrylate oligomer exceeds 2,000, the surface hardness is low and the antistatic performance is degraded due to the increase in molecular weight.
[0053] It is preferable that such photopolymerizable urethane acrylate oligomers be included in an amount of 10 to 40 weight percent of the total weight of the antistatic coating layer (140). If the photopolymerizable urethane acrylate oligomers are less than 10 weight percent of the total weight of the antistatic coating layer (140), it may be difficult to ensure durability, and if they exceed 40 weight percent, there is a risk that the antistatic performance may be reduced.
[0054] The conductive polymer includes one or more selected from polyaniline, polypyrrole, polythiophene, poly(3,4-ethylenethiophene), derivatives thereof, and copolymers thereof. In the present invention, polyethylenedioxythiophene (PEDOT), a derivative of polythiophene, was used as the conductive polymer.
[0055] It is preferable that the conductive polymer be added in a content ratio of 10 to 50 weight percent of the total weight of the antistatic coating layer (140), and more preferable that it be added in a content ratio of 20 to 40 weight percent. If the amount of conductive polymer added is less than 10 weight percent of the total weight of the antistatic coating layer (140), it is difficult to properly exhibit the antistatic effect, and if it exceeds 50 weight percent, there is a problem of reduced strength.
[0056] The antistatic coating layer (140) preferably has a thickness of 10 to 500 nm, and a more preferable range may be a thickness of 100 to 400 nm. If the thickness of the antistatic coating layer (140) is too thin, less than 10 nm, it is difficult to properly exert the antistatic effect, and if the thickness of the antistatic coating layer (140) is formed too thick, exceeding 500 nm, there is a problem of reducing strength.
[0057] Additionally, the antistatic coating layer (140) may further include one or more of 0.1 to 2.0 weight% of propylene glycol monomethyl ether and 0.1 to 1.5 weight% of 2-methacryloyloxyethyl phosphate.
[0058] Propylene glycol monomethyl ether is added to the antistatic coating layer (140) to increase elongation without reducing strength. If the amount of propylene glycol monomethyl ether added is less than 0.1% by weight of the total weight of the antistatic coating layer (140), the amount added is negligible and it is difficult to properly exert the effect of increasing elongation, and if it is added in excess of 2.0% by weight, there is a risk of reducing strength.
[0059] 2-methacryloyloxyethyl phosphate is added to the antistatic coating layer (140) to increase strength while minimizing the reduction in elongation. If the amount of 2-methacryloyloxyethyl phosphate added is less than 0.1% by weight of the total weight of the antistatic coating layer (140), it is difficult to achieve a strength-enhancing effect, and if it is added in excess of 1.5% by weight, it may act as a factor that increases the surface resistance value.
[0060] As described above, the PET wig yarn with excellent mechanical properties and antistatic properties according to the embodiment of the present invention is manufactured into a filament using a master chip containing PET resin as a main component, and while having excellent mechanical properties and curling properties, an antistatic coating layer covering the surface of the PET resin is formed to improve antistatic properties and durability.
[0061] In addition, the PET wig yarn according to the embodiment of the present invention, which has excellent mechanical properties and antistatic properties, has an excellent antistatic effect due to the antistatic coating layer covering the surface of the wig yarn body. Therefore, it can prevent the problem of the wig hair lifting up due to static electricity in advance, and also improve curl retention and curl elasticity by ensuring excellent mechanical properties and curling ability through superior strength and durability.
[0062] As a result, the PET wig yarn according to the embodiment of the present invention, which has excellent mechanical properties and antistatic properties, exhibits a strength of 3.5 to 4.0 g / de and an elongation of 70 to 75% when the fineness is 50 denier (de), thereby exhibiting excellent curl formation properties as well as excellent curl retention properties.
[0063] Hereinafter, a method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention will be described with reference to the attached drawings.
[0064] FIG. 2 is a process flowchart showing a method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention.
[0065] As shown in FIG. 2, a method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention includes a raw material preparation step (S110), a compression and spinning step (S120), a drafting step (S130), and a coating and drying step (S140).
[0066] Raw material preparation stage
[0067] In the raw material preparation step (S110), a master chip is prepared comprising 20 to 40 wt% flame retardant, 0.1 to 5.0 wt% heat stabilizer, 0.1 to 3.0 wt% process stabilizer, 5 to 15 wt% strength reinforcing agent, and the remainder being PET resin.
[0068] Flame retardants can be used by mixing one or two types selected from phosphorus-based flame retardants and polymeric bromine-based flame retardants, and more preferably, polymeric bromine-based flame retardants are used.
[0069] Heat stabilizers and process stabilizers are added to minimize the generation of radicals, which are resin pyrolysis products, to improve compatibility between PET resin and flame retardants, and to prevent the flame retardant from adhering to metal surfaces such as cylinders, screws, and nozzles of melt extruders. In this case, Irganox 1010 may be used as a heat stabilizer and Struktol TR 065 may be used as a process stabilizer, but are not limited thereto. Significant improvement effects can be obtained when using polybromoepoxy flame retardants or polybromophenoxy flame retardants with these heat stabilizers and process stabilizers.
[0070] Strength reinforcing agents are added to reinforce strength. These strength reinforcing agents include one or more selected from talc, alumina, calcium carbonate, magnesium carbonate, magnesia, calcium silicate, glass fiber, titanium oxide, and antimony oxide.
[0071] Such strength reinforcing agents may include a first strength reinforcing agent having an average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm. In this case, it is preferable to add 60 to 80 weight% of the first strength reinforcing agent and 20 to 40 weight% of the second strength reinforcing agent. In this way, when a first strength reinforcing agent having a relatively small average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm, which is relatively larger than the first strength reinforcing agent, are mixed and added, the dispersibility of the relatively large second strength reinforcing agent and the relatively small first strength reinforcing agent is greatly improved, thereby improving strength uniformity.
[0072] The PET (polyethylene terephthalate) resin comprises a high-viscosity PET (polyethylene terephthalate) resin with an intrinsic viscosity of 0.75 to 0.90 and a low-viscosity PET resin with an intrinsic viscosity of 0.50 to 0.60, wherein it is preferable to comprise 80 to 95 weight% of the high-viscosity PET resin and 5 to 20 weight% of the low-viscosity PET resin.
[0073] It is more preferable to use a mixture of high-viscosity and low-viscosity PET (polyethylene terephthalate) resins, wherein the difference in intrinsic viscosity is 0.15 to 0.25, most preferably 0.17 to 0.22. At this time, if the difference in intrinsic viscosity is less than 0.15 or exceeds 0.25, it may be difficult to obtain the desired curling properties and mechanical properties.
[0074] Compression and radiation stages
[0075] In the compression and spinning step (S120), the master chip is supplied to the spinneret in a state of melting and mixing, and then compressed and spun to form a filament.
[0076] In this step, the master chip can be resinified by melting and kneading it at 270 to 330°C.
[0077] Drafting stage
[0078] In the drafting step (S130), the filament is drafted at a draft rate of 10 to 50 times.
[0079] Draft refers to the elongation rate of the yarn from the time the molten polymer exits the nozzle hole until it is wound. In other words, it can be expressed as the discharge speed and spinning speed of the molten polymer at the nozzle hole. At this time, the draft ratio is important to ensure uniform fineness. If the draft ratio is less than 10 times, productivity decreases significantly, and since it is difficult to control yarn shaking directly below the nozzle, the occurrence of yarn breakage actually increases. If the draft ratio exceeds 50 times, the occurrence of yarn breakage increases, and problems with uneven fineness occur, resulting in a significant decrease in strength and making it difficult to use as wig yarn.
[0080] Coating and drying steps
[0081] In the coating and drying step (S140), an antistatic coating composition is coated on the surface of the drafted filament, and then dried to form an antistatic coating layer.
[0082] Here, the antistatic coating layer comprises 10 to 30 wt% of a reactive monomer, 1 to 10 wt% of a photoinitiator, 5 to 25 wt% of an antistatic agent, 0.1 to 3 wt% of a leveling agent, 10 to 40 wt% of a photopolymerizable urethane acrylate oligomer, and the remainder being a conductive polymer.
[0083] The reactive monomer may have one or more acrylate, methacrylate, or vinyl groups in its molecular structure and may be a monomer having 1 to 3 functional groups or more various functional groups, and the amount of 1 to 3 functional monomers, etc., may be adjusted considering the working viscosity, substrate adhesion, and scratch resistance of the resin composition. In addition, it is desirable for the reactive monomer to have high tensile strength and a low curing shrinkage rate.
[0084] The photoinitiator may be a benzophenone-based compound such as 1-hydroxycyclohexylphenyl ketone. More specifically, the photoinitiator may be acetophenones, benzophenones, miclerbenzoylbenzoate, α-amyloxime esters, and thioxantones, but is not limited thereto.
[0085] Antistatic agents are added to prevent the generation of static electricity. Such antistatic agents may include one or more selected from non-ionic amine-based antistatic agents, polyhydric alcohol fatty acid ester antistatic agents, non-ionic amino-based antistatic agents, aliphatic amide-based antistatic agents, ionic-based antistatic agents, ionic polymer-based antistatic agents, quaternary ammonium-based antistatic agents, ionic complex-based antistatic agents, lithium amide-based antistatic agents, and photocurable antistatic agents.
[0086] The leveling agent serves to provide surface smoothness and surface slip function, while simultaneously improving scratch resistance. Such leveling agents may include one or more selected from silicone acrylate-based leveling agents, non-silicone acrylate-based leveling agents, and acrylate polysiloxane-based leveling agents.
[0087] It is preferable to use a photopolymerizable urethane acrylate oligomer having 2 to 6 functional groups and a weight-average molecular weight (Mw) within 1,000 to 2,000. If the weight-average molecular weight (Mw) of the photopolymerizable urethane acrylate oligomer is less than 1,000, the antistatic coating layer is prone to cracking and has poor adhesion, and if the weight-average molecular weight (Mw) of the photopolymerizable urethane acrylate oligomer exceeds 2,000, the surface hardness is low and the antistatic performance is degraded due to the increase in molecular weight.
[0088] The conductive polymer includes one or more selected from polyaniline, polypyrrole, polythiophene, poly(3,4-ethylenethiophene), derivatives thereof, and copolymers thereof. In the present invention, polyethylenedioxythiophene (PEDOT), a derivative of polythiophene, was used as the conductive polymer.
[0089] It is preferable for such an antistatic coating layer to have a thickness of 10 to 500 nm, and a more preferable range may be a thickness of 50 to 300 nm. If the thickness of the antistatic coating layer is too thin, less than 10 nm, it is difficult to properly exhibit the antistatic effect, and if the thickness of the antistatic coating layer is formed too thick, exceeding 500 nm, there is a problem of reducing strength.
[0090] In addition, the antistatic coating layer may further include one or more of 0.1 to 2.0 weight% of propylene glycol monomethyl ether and 0.1 to 1.5 weight% of 2-methacryloyloxyethyl phosphate.
[0091] Propylene glycol monomethyl ether is added to an antistatic coating layer to increase elongation without reducing strength. If the amount of propylene glycol monomethyl ether added is less than 0.1% by weight of the total weight of the antistatic coating layer, the amount added is negligible, making it difficult to properly exhibit the effect of increasing elongation, and if it is added in excess of 2.0% by weight, there is a risk of reducing strength.
[0092] 2-methacryloyloxyethyl phosphate is added to the antistatic coating layer to increase strength while minimizing the reduction in elongation. If the amount of 2-methacryloyloxyethyl phosphate added is less than 0.1 weight% of the total weight of the antistatic coating layer, it is difficult to achieve a strength-enhancing effect, and if it is added in excess of 1.5 weight%, it may act as a factor that increases the surface resistance value.
[0093] In this step, one or more methods selected from spin coating, spray coating, roll coating, comma coating, etc. may be used for coating, but the present invention is not limited to these methods.
[0094] In addition, it is desirable to perform drying at 70 to 90°C for 1 to 20 hours. If the drying temperature is below 70°C or the drying time is less than 1 hour, sufficient drying may not be achieved, making it difficult to secure strength. If the drying temperature exceeds 90°C or the drying time exceeds 20 hours, it may act as a factor that only increases manufacturing costs without further increasing the effect, making it uneconomical.
[0095] In addition, the PET wig yarn of the present invention exhibits a strength of 3.5 to 4.0 g / de and an elongation of 70 to 75% when the fineness is 50 denier (de). Furthermore, the PET wig yarn of the present invention not only has excellent curl-forming properties but also excellent curl retention properties.
[0096] As described above, the method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention can improve antistatic properties and durability by manufacturing it into a filament using a master chip containing PET resin as a main component, thereby having excellent mechanical properties and curling properties, while also forming an antistatic coating layer that covers the surface of the PET resin.
[0097] In addition, the method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to an embodiment of the present invention has an excellent antistatic effect due to the antistatic coating layer covering the surface of the wig yarn body, so it can prevent the problem of wig hair lifting up due to static electricity in advance, and also improve curl retention and curl elasticity by securing excellent mechanical properties and curling properties with superior strength and durability.
[0098] As a result, the method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties according to the embodiment of the present invention exhibits a strength of 3.5 to 4.0 g / de and an elongation of 70 to 75% when the fineness is 50 denier (de), thereby exhibiting excellent curl formation properties as well as excellent curl retention properties.
[0099] Examples
[0100] Hereinafter, the structure and operation of the present invention will be explained in more detail through preferred embodiments of the present invention. However, these are presented as preferred examples of the present invention and should not be interpreted in any way as limiting the present invention.
[0101] Details not listed here can be sufficiently technically inferred by a person skilled in this field, so their explanation will be omitted.
[0102] 1. PET wig yarn manufacturing
[0103] Example 1
[0104] A master chip was prepared comprising 27 wt% of polybromoepoxy (Mw=70,000, bromine content about 67.8 wt%) composed of a polymer of brominated bisphenol A diglycidyl ether and brominated bisphenol A as a flame retardant, 1.5 wt% of a heat stabilizer (product name: Irganox 1010), 1.0 wt% of a process stabilizer (product name: Stuttukt 065), 10 wt% of alumina (Al2O3) as a strength reinforcing agent, and the remainder being PET resin. Here, as a strength reinforcing agent, a mixture of 75 wt% alumina (Al2O3) with an average diameter of 2.0 μm and 25 wt% alumina (Al2O3) with an average diameter of 6.0 μm was used, and as a PET resin, a mixture of high viscosity PET resin with an intrinsic viscosity (IV) of 0.80 and low viscosity PET resin with an intrinsic viscosity (IV) of 0.55 was used, specifically a mixture of 91 wt% high viscosity PET resin and 9 wt% low viscosity PET resin.
[0105] Next, the master chip was melted and kneaded at 280°C to form a resin, then fed into a spinneret, and compressed and spun to produce a filament.
[0106] Next, a PET wig yarn was manufactured by drafting the filament at a draft rate of 20 times, spray-coating an antistatic coating composition onto the surface of the drafted filament, and drying at 85°C for 15 hours to form an antistatic coating layer with a thickness of 350 nm. Here, the antistatic coating composition used was prepared by adding a mixture composed of 20 wt% of 2-phenoxyethyl acrylate as a reactive monomer, 3 wt% of miclur benzoyl benzoate as a photoinitiator, 10 wt% of a nonionic amino-based antistatic agent as an antistatic agent, 1.0 wt% of a non-silicone acrylate-based leveling agent as a leveling agent, 25 wt% of a photopolymerizable urethane acrylate oligomer, and the remainder of polyethylenedioxythiophene (PEDOT) to propylene glycol monomethyl ether acetate (PGMEA), a solvent, in a volume ratio of 1:2, and then stirring at a speed of 1,500 rpm for 1 hour.
[0107] Example 2
[0108] PET wig yarn was manufactured in the same manner as in Example 1, except that 13 wt% of alumina (Al2O3) was added as a strength reinforcing agent, and a mixture of 80 wt% of alumina (Al2O3) with an average diameter of 1.5 μm and 20 wt% of alumina (Al2O3) with an average diameter of 5.5 μm was used.
[0109] Example 3
[0110] A PET wig yarn was manufactured in the same manner as in Example 1, except that 16 wt% of calcium carbonate (CaCO3) was added as a strength reinforcing agent, and a mixture of 82 wt% of calcium carbonate (CaCO3) with an average diameter of 2.0 μm and 18 wt% of calcium carbonate (CaCO3) with an average diameter of 5.4 μm was used.
[0111] Example 4
[0112] A PET wig yarn was manufactured in the same manner as in Example 1, except that the PET resin used was a mixture of a high-viscosity PET resin with an intrinsic viscosity (IV) of 0.83 and a low-viscosity PET resin with an intrinsic viscosity (IV) of 0.57, with the mixture being 88 wt% high-viscosity PET resin and 12 wt% low-viscosity PET resin.
[0113] Example 5
[0114] A PET wig yarn was manufactured in the same manner as in Example 1, except that the PET resin used was a mixture of a high-viscosity PET resin with an intrinsic viscosity (IV) of 0.81 and a low-viscosity PET resin with an intrinsic viscosity (IV) of 0.51, with the mixture being 85 wt% high-viscosity PET resin and 15 wt% low-viscosity PET resin.
[0115] Example 6
[0116] PET wig yarn was prepared in the same manner as in Example 1, except that 1.5 wt% of propylene glycol monomethyl was further added to the antistatic coating composition.
[0117] Example 7
[0118] PET wig yarn was prepared in the same manner as in Example 1, except that 1.2 wt% of propylene glycol monomethyl and 0.9 wt% of 2-methacryloyloxyethyl phosphate were further added to the antistatic coating composition.
[0119] Comparative Example 1
[0120] A second master chip was prepared comprising 10 wt% of polybromoepoxy (Mw=70,000, bromine content about 67.8 wt%) composed of a polymer of brominated bisphenol A diglycidyl ether and brominated bisphenol A as a flame retardant, 1.5 wt% of a heat stabilizer (product name: Irganox 1010), 0.5 wt% of a process stabilizer (product name: Stuttukt 065), 4 wt% of alumina (Al2O3) with an average diameter of 5.3 μm as a strength reinforcing agent, and the remainder being PET resin. Here, as the PET resin, a mixture of high-viscosity PET resin with an intrinsic viscosity (IV) of 0.80 and low-viscosity PET resin with an intrinsic viscosity (IV) of 0.55 was used, with a mixture of 91 wt% high-viscosity PET resin and 9 wt% low-viscosity PET resin.
[0121] Next, the master chip was fed into a spinneret maintained at 250°C, and then compressed and spun to produce a filament.
[0122] Next, PET wig yarn was manufactured by drafting the filament at a draft rate of 20 times.
[0123] Comparative Example 2
[0124] PET wig yarn was manufactured using the same method as Comparative Example 1, except that 11 wt% of calcium carbonate (CaCO3) with an average diameter of 3.5 μm was added as a strength reinforcing agent.
[0125] Comparative Example 3
[0126] A PET wig yarn was manufactured in the same manner as Comparative Example 1, except that the PET resin used was a mixture of a high-viscosity PET resin with an intrinsic viscosity (IV) of 0.81 and a low-viscosity PET resin with an intrinsic viscosity (IV) of 0.51, with the mixture being 85 wt% high-viscosity PET resin and 15 wt% low-viscosity PET resin.
[0127] 2. Evaluation of physical properties
[0128] Tables 1 and 2 show the results of the physical property evaluation of PET wig yarns prepared according to Examples 1 to 7 and Comparative Examples 1 to 3.
[0129] 1) Robbers and believers
[0130] Measurements were taken using an automatic tensile testing machine (Textechno) at a speed of 50 cm / min and a gripping distance of 50 cm. Strength and elongation were defined as the value (g / de) obtained by dividing the applied load by the denier (de) when the fiber is stretched by applying a constant force until it breaks, and elongation as the value (%) representing the initial length as a percentage of the elongated length.
[0131] 2) Curl formation and curl retention
[0132] Curl formation was evaluated by cutting a bundle of 40,000 denier (160 strands × 50 denier × 5 strands) wig yarn into a length of 30 cm, securing it with a clamp, wrapping it 5 times around an electric curling iron heated to 200°C, holding it for 5 seconds, and then removing the iron to assess the curl state immediately after formation. This was based on the curl-forming length of wig yarn made from 100 parts by weight of natural hair. (◎: Same as the curl-forming length of synthetic wig yarn made from natural hair, ○: Lengthened by 1 to 2 cm compared to the standard, △: Lengthened by 3 to 4 cm compared to the standard, ×: Lengthened by 5 cm or more compared to the standard)
[0133] Curl retention was evaluated by assessing whether the formed curls were maintained after repeating the washing and drying of the wig yarn used for the curl formation evaluation with cold water 10 times. (◎: Very good curl retention, ○: Good curl retention, △: Average, ×: Curl loosened)
[0134] 3) Long-term heat resistance (min): The oxidation onset time at 200℃ was measured using OIT (Oxygen induced time).
[0135] 4) Surface resistance measurement
[0136] Surface resistance was measured using a sheet resistance meter.
[0137] 5) Haze measurement
[0138] The haze value was measured using a colorimeter.
[0139] 6) Number of rejections
[0140] The number of yarn breakage occurrences over 24 hours during the manufacturing process using composite spinning was measured by counting.
[0141] division Example 1 Example 2 Example 3 Example 4 Example 5 Strength (g / de) 3.52 3.57 3.60 3.59 3.61 believers (%) 73.4 73.6 73.5 72.9 73.6 Curl formation ◎ ◎ ◎ ◎ ◎ Curl retention ◎ ◎ ◎ ◎ ◎ Long-term heat resistance (min) 107 108 109 107 108 Surface resistance (Ω / sq.) 2.7 × 10 10 2.5 × 10 10 2.9 × 10 10 3.1 × 10 10 2.8 × 10 10 Haze value (%) 2.56 2.59 2.61 2.62 2.58 Number of rejections (times / 24 hours) 0 0 0 1 0
[0142] division Example 6 Example 7 Comparative Example 1 Comparative Example 2 Comparative Example 3 Strength (g / de) 3.84 3.92 3.12 3.25 3.36 believers (%) 71.7 72.8 73.1 72.6 71.9 Curl formation ◎ ◎ △ △ × Curl retention ◎ ◎ △ × △ Long-term heat resistance (min) 110 112 101 98 103 Surface resistance (Ω / sq.) 1.7 × 10 10 1.3 × 10 10 5.5 × 10 11 4.7 × 10 12 4.2 × 10 12 Haze value (%) 2.74 2.96 12.31 11.52 9.57 Number of rejections (times / 24 hours) 0 0 6 5 5
[0143] As shown in Tables 1 and 2, the PET wig yarns according to Examples 1 to 7 had excellent mechanical properties with a strength of 3.5 g / de or more and an elongation of 70% or more, as well as excellent curl formation and curl retention, and excellent long-term heat resistance, and it was confirmed that the productivity was excellent as the number of yarn cuts was measured to be 1 or less.
[0144] On the other hand, compared to Examples 1 to 7, the PET wig yarn according to Comparative Examples 1 to 3 had lower strength, poor curl formation, poor curl retention, and poor long-term heat resistance, and the number of yarn cuts was measured to be 5 or more, indicating poor productivity.
[0145] In addition, it was confirmed that the PET wig yarn according to Examples 1 to 7 exhibited significantly lower surface resistance and haze values compared to the PET wig yarn according to Comparative Examples 1 to 3, thereby demonstrating an excellent antistatic effect.
[0146] In particular, it can be confirmed that the mechanical properties of the PET wig yarn according to Examples 6 and 7 were measured at the highest values and the surface resistance was measured at the lowest values, which is attributed to the addition of one or more of propylene glycol monomethyl ether and 2-methacryloyloxyethyl phosphate.
[0147] Although the embodiments and comparative examples of the present invention have been described in detail as above, the scope of the present invention is not limited thereto, and the scope of the present invention extends to those that are substantially equivalent to the embodiments of the present invention. Explanation of the symbols
[0148] 100 : PET wig yarn 120 : Wig yarn body 140: Antistatic coating layer S110: Raw material preparation stage S120: Compression and radiation steps S130: Drafting Phase S140: Coating and drying steps
Claims
Claim 1 A wig yarn body comprising 20 to 40 wt% flame retardant, 0.1 to 5.0 wt% heat stabilizer, 0.1 to 3.0 wt% process stabilizer, 5 to 15 wt% strength reinforcing agent, and the remainder being PET resin; and an antistatic coating layer formed to cover the surface of the wig yarn body, comprising 10 to 30 wt% of a reactive monomer, 1 to 10 wt% of a photoinitiator, 5 to 25 wt% of an antistatic agent, 0.1 to 3 wt% of a leveling agent, 10 to 40 wt% of a photopolymerizable urethane acrylate oligomer, 0.1 to 2.0 wt% of propylene glycol monomethyl ether, 0.1 to 1.5 wt% of 2-methacryloyloxyethyl phosphate, and the remainder being a conductive polymer; wherein the strength reinforcing agent comprises one or more selected from talc, alumina, calcium carbonate, magnesium carbonate, magnesia, calcium silicate, glass fiber, titanium oxide, and antimony oxide, and wherein the strength reinforcing agent comprises a first strength reinforcing agent having an average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm, wherein the first strength reinforcing agent A PET wig yarn having excellent mechanical properties and antistatic properties, characterized by being added in an amount of 60 to 80 weight% and 20 to 40 weight% of a second strength reinforcing agent, wherein the reactive monomer comprises one or more selected from 2-hydroxypropyl (meth)acrylate, 2-phenoxyethyl acrylate, ethylene oxide addition type phenoxyethyl acrylate, 2-(2-ethoxy)ethyl acrylate, nonylphenyl acrylate, epoxy monoacrylate, and oxyethylphenol acrylate, wherein the photopolymerizable urethane acrylate oligomer has 2 to 6 functional groups and a weight-average molecular weight (Mw) of 1,000 to 2,000, and the antistatic coating layer has a thickness of 100 to 400 nm. Claim 2 delete Claim 3 A PET wig yarn having excellent mechanical properties and antistatic properties, characterized in that, in claim 1, the PET resin comprises a high-viscosity PET (polyethylene terephthalate) resin having an intrinsic viscosity of 0.75 to 0.90 and a low-viscosity PET resin having an intrinsic viscosity of 0.50 to 0.60, wherein the high-viscosity PET resin comprises 80 to 95 weight% and the low-viscosity PET resin comprises 5 to 20 weight%. Claim 4 delete Claim 5 A PET wig yarn with excellent mechanical properties and antistatic properties according to claim 1, characterized in that the conductive polymer comprises one or more selected from polyaniline, polypyrrole, polythiophene, poly(3,4-ethylenethiophene), derivatives thereof, and copolymers thereof. Claim 6 (a) a step of preparing a master chip comprising 20 to 40 wt% flame retardant, 0.1 to 5.0 wt% heat stabilizer, 0.1 to 3.0 wt% process stabilizer, 5 to 15 wt% strength reinforcing agent, and the remainder being PET resin; (b) a step of supplying the master chip to a spinneret in a molten and kneaded state, and then compressing and spinning to form a filament; (c) a step of drafting the filament at a draft ratio of 10 to 50 times; and (d) a step of forming an antistatic coating layer by coating an antistatic coating composition on the surface of the drafted filament and then drying; wherein, in step (d), the antistatic coating layer comprises 10 to 30 wt% reactive monomer, 1 to 10 wt% photoinitiator, 5 to 25 wt% antistatic agent, 0.1 to 3 wt% leveling agent, 10 to 40 wt% photopolymerizable urethane acrylate oligomer, 0.1 to 2.0 wt% propylene glycol monomethyl ether, and 0.1 to 1 wt% 2-methacryloyloxyethyl phosphate.It comprises 5 wt% and the remainder being a conductive polymer, wherein the strength reinforcing agent comprises one or more selected from talc, alumina, calcium carbonate, magnesium carbonate, magnesia, calcium silicate, glass fiber, titanium oxide, and antimony oxide, wherein the strength reinforcing agent comprises a first strength reinforcing agent having an average diameter of 1 to 3 μm and a second strength reinforcing agent having an average diameter of 5 to 7 μm, added in an amount of 60 to 80 wt% of the first strength reinforcing agent and 20 to 40 wt% of the second strength reinforcing agent, wherein the reactive monomer comprises one or more selected from 2-hydroxypropyl (meth)acrylate, 2-phenoxyethyl acrylate, ethylene oxide addition type phenoxyethyl acrylate, 2-(2-ethoxy)ethyl acrylate, nonylphenyl acrylate, epoxy monoacrylate, and oxyethylphenol acrylate, and the photopolymerizable urethane acrylate oligomer comprises 2 ~ A method for manufacturing PET wig yarn having excellent mechanical properties and antistatic properties, characterized in that a material having 6 functional groups and a weight-average molecular weight (Mw) of 1,000 to 2,000 is used, and the antistatic coating layer has a thickness of 100 to 400 nm. Claim 7 A method for manufacturing a PET wig yarn having excellent mechanical properties and antistatic properties, characterized in that, in step (a) above, the PET resin comprises a high-viscosity PET (polyethylene terephthalate) resin having an intrinsic viscosity of 0.75 to 0.90 and a low-viscosity PET resin having an intrinsic viscosity of 0.50 to 0.60, wherein the high-viscosity PET resin comprises 80 to 95 weight% and the low-viscosity PET resin comprises 5 to 20 weight%. Claim 8 delete Claim 9 A method for manufacturing PET wig yarn with excellent mechanical properties and antistatic properties, characterized in that, in step (d) above, the conductive polymer comprises one or more selected from polyaniline, polypyrrole, polythiophene, poly(3,4-ethylenethiophene), derivatives thereof, and copolymers thereof.
Citation Information
Patent Citations
Ultraviolet-curable coating composition
JP2006052356A
Fibers for artificial hair, method for producing same, and hair accessory
US20240035231A1
Ultra violet curing hard coating composition having anti-smudge and anti-static properties
KR1020120115883A
Complex yarn for high strength sheath-coe type wig raw yarn having antistatic effect and manufacturing method thereof
KR1020240085250A
